1971
DOI: 10.1002/anie.197105481
|View full text |Cite
|
Sign up to set email alerts
|

The Anomalous Temperature Dependence of Enzyme‐Catalyzed Reactions

Abstract: Breaks or curvatures in the plot of log vbr us. IIT have been described in the literature for a number of reactions. If sufficiently small temperature intervals are used in the investigation of the temperature dependence (STI method) a trend line is obtained instead. It is then possible to distinguish regions of linear behavior and regions of anomalous behavior. The effects of e. g . the p H , the ionic strength, and added salts as well as of the size of the enzyme and substrate molecules on the anamalies were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

1973
1973
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 28 publications
0
11
1
Order By: Relevance
“…However, they also reported that the block produced by Dibenamine or POB at 70 C did not persist after the temperature was raised to 240 C. The reason for this discrepancy is not entirely clear. However, it is known that haloalkylamines block a-adrenoceptors in two steps, a relatively labile approximation to the receptors and a subsequent stable alkylation that develops slowly (Nickerson, 1957 (Talsky, 1971), and it is tempting to speculate that the two classes of adrenergic receptors may represent allosteric configurations of the same structure. It is well known that the properties of allosteric enzymes can be influenced by compounds unrelated to the specific substrate, and allosteric adrenoceptors could appropriately be influenced by the 'modulator' substance that has been reported to alter the balance of a-and fl-adrenoceptor components of responses of skeletal muscle blood vessels of dogs (Szentivanyi, Kunos & Juhasz-Nagy, 1970) and by thyroid hormone (Kunos, Vermes-Kunos & Nickerson, 1974).…”
Section: Effects Of Phentolamine On Block By and Binding Of [3h]pobmentioning
confidence: 99%
“…However, they also reported that the block produced by Dibenamine or POB at 70 C did not persist after the temperature was raised to 240 C. The reason for this discrepancy is not entirely clear. However, it is known that haloalkylamines block a-adrenoceptors in two steps, a relatively labile approximation to the receptors and a subsequent stable alkylation that develops slowly (Nickerson, 1957 (Talsky, 1971), and it is tempting to speculate that the two classes of adrenergic receptors may represent allosteric configurations of the same structure. It is well known that the properties of allosteric enzymes can be influenced by compounds unrelated to the specific substrate, and allosteric adrenoceptors could appropriately be influenced by the 'modulator' substance that has been reported to alter the balance of a-and fl-adrenoceptor components of responses of skeletal muscle blood vessels of dogs (Szentivanyi, Kunos & Juhasz-Nagy, 1970) and by thyroid hormone (Kunos, Vermes-Kunos & Nickerson, 1974).…”
Section: Effects Of Phentolamine On Block By and Binding Of [3h]pobmentioning
confidence: 99%
“…Sharp breaks in the Arrhenius diagram and other temperature de pendent anomalies of various enzyme reactions have been reported, and a11o-steric changes in the conformation of the enzymes have been invoked to explain these phenomena (Talsky, 1971). Similar1y, the temperature sensitive transformation of an estrogen binding protein in the cytoso1 of rat uterus is thought to involve allosteric changes that permit migration of the receptor protein to the cell nucleus (Jensen et ~., 1968;Shyamala and Gorski, 1969 Kunos and Szentivanyi (1968) also noted the difference between winter and summer frog hearts and reported that it required combination of a metabolic inhibitor (2,4-dinitrophenol) and cooling to al10w block by a-adrenergic antagonists in the latter.…”
Section: \mentioning
confidence: 99%
“…Moreover, a change in the rate‐limiting step would have shown a curvature in Arrhenius plots rather than a clear break. Thus our results suggest that the enzyme may exist in two different active forms [ES] 1 ‡ and [ES] 2 ‡ on both sides of the break [28, 33]. This may reflect a temperature‐dependent plasticity of the substrate‐complexed active site gorge.…”
Section: Resultsmentioning
confidence: 84%
“…Information on the energetics of enzyme reactions and equilibria as a function of temperature can be obtained from analysis of Arrhenius and van’t Hoff plots, respectively. In particular, the existence of breaks in Arrhenius plots can account for small changes in conformation, changes in reaction mechanism, and phase transition of lipids bound to enzymes [28–33]. The present study allowed us to construct Arrhenius and van’t Hoff plots for the hydrolysis of BuSCh by BuChE and its D70G mutant at different pressures.…”
mentioning
confidence: 96%